The Influence Of Financing And Third Party Funds (Dpk) Towards Roa Of Islamic Rural Banks (Bprs) In Sumatera Barat - Rizal, Rizal; Khairi, Khairil Faizal; Nengsih, Ifelda (Universitas Islam Negeri Raden Intan Lampung, 2020)
This research aims to investigate the influence of financing and Third Party Funds (DPK) towards the Return on Assets (ROA) of Islamic Rural Banks (BPRS) in West Sumatera. This field research is a quantitative study with seven PT BPRS in West Sumatera as the object of the research. This research uses secondary data in the form of panel data which combined cross section and time series data. The panel data are quarterly financial statements from 2016 to 2018 which are recorded in Financial Service Authority (OJK). The result of this research shows financing and third party funds (DPK) influence ROA in the amount of 59,65% simultaneously. The rest of it are influenced by other factors that are not investigated. Partially, financing is the only subject that has influence toward ROA. Meanwhile, third party funds had no significant influence towards ROA of seven BPRS in West Sumatera. This case is interesting to be researched since quantitative data reflects fluctuation based on financing from 2016 until 2018 while DPK tend to increase. However, financing is the only subject that has significant influence towards ROA.